Effect of Surface Morphology and Elemental Composition on the Magnetization Behaviour of Electrodeposited NiFe Films - Musaab Salman Sultan (Journal of Nanotechnology)
The effect of surface morphology and elemental composition on the magnetic properties of nickel-iron (NiFe) films prepared by electrodeposition with a range of deposition times has been investigated using a high-resolution scanning electron microscope, energy and wavelength dispersive X-ray analysis, and magneto-optical Kerr effect magnetometry. Defects were noticed with various sizes distributed randomly in these samples. There was a noticeable increase in the defect size with a decrease in the deposition time. A slight variation in the elemental composition across the sample area was noticed. Very limited variation in the elemental weight with deposition time was seen. Square hysteresis loops were obtained from most locations on these samples with a high remanent magnetization. A reduction in coercivity was observed with increasing sample thickness. A wide distribution of the coercivity across the sample area and a slight change in the shape of the loops were seen, especially with samples with shorter deposition times. This was attributed to the differences in the film’s elemental composition or the surface variation, which can act as pinning centers during the domain wall reversal. These defects have a more significant effect at shorter deposition times, which increases the coercivity of such films. This article gives an indication that NiFe films produced by this technique under such conditions are nonuniform, soft at longer growth times, and largely isotropic. Thus, in order to use such films in magnetic devices, their quality needs to be improved.